Endothelial and platelet microparticles in vasculitis of the young. - Brogan, P; Shah, V; Brachet, C; Harnden, A; Mant, D; Klein, N; Dillon, M (2004)
OBJECTIVE: Microparticles are released from endothelial cells in response to a variety of injurious stimuli and recently have been shown to be increased in a number of diseases associated with endothelial dysfunction. This study examined endothelial microparticle (EMP) and platelet microparticle (PMP) profiles in children with systemic vasculitis to test the hypothesis that EMPs may provide a noninvasive means of examining endothelial activation or injury. METHODS: The study cohort comprised 39 children with systemic vasculitis at various stages of disease activity, 24 control children with febrile disease, and a control group of 43 healthy subjects. Plasma was ultracentrifuged at 17,000g for 60 minutes, and the microparticle pellets were examined using flow cytometry. RESULTS: Plasma from patients with active systemic vasculitis contained significantly higher numbers of E-selectin-positive EMPs compared with that from patients in remission, healthy controls, or febrile disease controls (P = 0.000 for each). A similar result was obtained for the numbers of EMPs expressing the marker CD105. There was also a significant increase in PMPs expressing CD42a in the active vasculitis group as compared with the other groups, but this difference was not significant for PMPs expressing P-selectin. The EMP counts correlated with the Birmingham Vasculitis Activity Score and the acute-phase reactant levels in the patients with systemic vasculitis, but there was a poor correlation overall between EMP counts and the acute-phase reactant levels in the febrile disease controls. CONCLUSION: EMPs may provide a window to the activated endothelium and could provide important pathophysiologic insights into the vascular injury associated with vasculitis of the young.